The Architecture and Liturgy of the Bema in Fourth- to-Sixth-Century Syrian Churches. - Loosley, Emma (Texts and studies in Eastern Christianity., 2012)
In fourth to sixth century Syria a nave-platform known as the Bema became popular in some regions before mysteriously disappearing; this study seeks to explain how these bemata functioned and which elements led to their decline.